2010
DOI: 10.4161/cc.9.9.11542
|View full text |Cite
|
Sign up to set email alerts
|

Dietary n-3 polyunsaturated fatty acids fail to reduce prostate tumorigenesis in the PB-ErbB-2 x Pten+/-preclinical mouse model

Abstract: Diet and obesity, and their associated metabolic alterations, are some of the fastest-growing causes of disease and death in America. Findings from epidemiological studies correlating obesity, the sources of dietary fat and prostate cancer (PCa) are conflicting. We have previously shown that 15% of PB-ErbB-2 x pten+/− mice developed PCa and exhibited increased phosphorylated 4E-BP1, but not the key PI3-kinase intermediary phospho-protein, mTOR, when maintained on unrefined mouse chow. We report herein that 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Numerous reports have shown that unsaturated FAs, such as docosahexaenoic acid and n‐3 polyunsaturated FAs (n‐3 PUFAs) induces apoptosis by upregulation of syndecan‐1 expression, and decreases phosphorylation of the 3‐phosphoinositide‐dependent kinase 1/AKT/Bad pathway . However, other studies also report that dietary n‐3 PUFAs fail to reduce tumor progression in PB‐ErbB‐2xPTEN(±) mice . The inconsistency might be oncogenic event dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous reports have shown that unsaturated FAs, such as docosahexaenoic acid and n‐3 polyunsaturated FAs (n‐3 PUFAs) induces apoptosis by upregulation of syndecan‐1 expression, and decreases phosphorylation of the 3‐phosphoinositide‐dependent kinase 1/AKT/Bad pathway . However, other studies also report that dietary n‐3 PUFAs fail to reduce tumor progression in PB‐ErbB‐2xPTEN(±) mice . The inconsistency might be oncogenic event dependent.…”
Section: Discussionmentioning
confidence: 99%
“…The slides were blocked for 20 min and incubated overnight at 4°C with the primary antibody. Detection was performed as previously described 13 , 31 - 34 . Because of the small sample size statistical analyses were performed using the Mann-Whitney U test and actual p values are shown.…”
Section: Methodsmentioning
confidence: 99%
“…158), although dietary n-3 polyunsaturated fatty acids failed to reduce prostate tumorigenesis in a preclinical mouse model. 159 A recent case-control study found a strong association between high intake of long chain n-3 PUFA and decreased risk of aggressive prostate cancer. 158 Furthermore, this study identified a SNP in the COX-2 gene that, along with low dietary intake of n-3 PUFA, had an increased risk of prostate cancer (OR = 5.49; 95% CI: 1.80-16.7).…”
Section: Pia As a Precursor Lesion To Prostate Cancermentioning
confidence: 99%
“…Just as proinflammatory n‐6 polyunsaturated fatty acids (PUFA) may confer an increased risk of prostate cancer, the anti‐inflammatory n‐3 (omega 3) PUFA has been associated with a decreased risk (reviewed in Ref. 158), although dietary n‐3 polyunsaturated fatty acids failed to reduce prostate tumorigenesis in a preclinical mouse model 159 . A recent case–control study found a strong association between high intake of long chain n‐3 PUFA and decreased risk of aggressive prostate cancer 158 .…”
Section: Anti‐inflammatory Compounds and Prostate Cancer Riskmentioning
confidence: 99%